(untitled) (Al-Academy, 2018)
In order to activate theatrical discourse aware of the changes imposed by the nature of the contemporary child in terms of stimulating the social skills that achieve a technical and aesthetic convergence between him and theatrical presentation by investing the fact of the existence of the child and its potential in the weaving of stories, and folk in the imagination, and simulation of what corresponds with the characters and icons interact with them through technologies In the light of this research came the following address: (ways to stimulate the skills of the child through a contemporary theatrical speech) where the researcher seeks to delineate the importance involved in the discourse of theater through ways to reach the pillars contribute to enhance the vision and stimulate the skills that make the child optimistic Ola and a sense of collective participatory